Correlation between Ketogenic Diet and Emotion Regulation in Early Adulthood - Hermawati, Nisa; Amandani, Purwanti; Meiza, Asti (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The purpose of this study is to determine whether there is a correlation between ketogenic diet and emotion regulation in early adulthood. One of the most common ways to get the ideal body weight is by diet. One of the popular diets is ketogenic diet with a composition of 60-70% fat, 15-30% protein, and 5-10% carbohydrate. Consuming excess fat will affect hormone balance and change emotion regulation. Methodology: This research uses a quantitative approach with data collection techniques using a Ketogenic Diet Scale and an Emotion Regulation Scale. Subjects were 393 early adults aged 26-35 years who are on a ketogenic diet for at least 1 month and never cheated from the rules of diet program. The two research variables are interval scale and the data analysis technique uses Pearson Correlation Test. Results: The results showed that there is a significant correlation between the ketogenic diet and the emotion regulation shown by r = -0,352, Pvalue =0,000, α =0,05 (Pvalue < α). This relationship means that the higher ketogenic diet related to the lower emotion regulation. The result is less in line with the goals of the ketogenic diet because the diet done without a doctor's supervision. Applications/Originality/Value: Emotion regulation is a skill related to self-management that should be mastered by early adulthood. The results of this study indicate that one can gain emotional regulation skills by using the ketogenic diet, as long as this diet is done properly and under the supervision of a doctor.